The Relationship between Tourism Development and the Gentrification Process in Pirenópolis (GO) - Belcavelo Silveira Marques, Ariane; Xavier, Wescley Silva; Theodoro Guedes, Leandro (Organizações & Sociedade, 2025)
This paper aims to understand the relationship between gentrification and the development of tourism in Pirenópolis-GO, based on the spatial configuration. It focuses, mainly, on the tourism policies integrated by the municipality and their consequences that encompass concrete and symbolic issues experienced by the individual in space. The paper is of qualitative nature, and data were collected from documentary research, semi-structured interviews and non-participant observation, analysed in the light of content analysis. The results allow us to affirm that state action focused on economic activities related to tourism overlap social, cultural, historical and environmental relations. Indeed, gentrification is expressed in concrete aspects with the removal of the marginalized population from that centre to increasingly distant areas in substitution for the business class coming from outside the city, and symbolic, since individuals begin to feel a loss of value cultural historical heritage and does not feel like an integral part of the new space designed for tourism.